Neurology-Neurorehabilitation 2016
DOI: 10.35841/neurology-neurorehabilitation.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Burden, its Predictors and Quality of Life in Caregivers of Stroke Survivors at Rural Community, Punjab, India

Abstract: Introduction: Stroke is a common neurological disorder characterized by long term dependency of patient on family members and need rehabilitation at home with consequent disturbances in certain areas of life of caregivers. The aim of the study was to examine specific nature of the burden and to estimate the relative influence of caregivers' characteristics on burden in caregivers.Methods: A cross sectional descriptive survey was carried out by recruiting 100 caregivers purposively in selected rural community s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Financial factors such as high monthly health-care bills and where the responsibility of paying such bills rested on CGs and/or SSs was also significantly associated with high CG burden, findings which were replicated in other studies. [5132436] These findings above are not out of place. In Nigeria, like a majority of developing countries, health-care financing is mostly out of pocket with scarce or poor health insurance coverage.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Financial factors such as high monthly health-care bills and where the responsibility of paying such bills rested on CGs and/or SSs was also significantly associated with high CG burden, findings which were replicated in other studies. [5132436] These findings above are not out of place. In Nigeria, like a majority of developing countries, health-care financing is mostly out of pocket with scarce or poor health insurance coverage.…”
Section: Discussionmentioning
confidence: 88%
“…These findings above have been replicated in other studies reviewed. [36373839] Regression analyses also predicted that for every point increase in Zarit burden score there was an almost four-fold increase in CGs performing more daily care tasks.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Many studies have examined the association between caregivers’ burden with patients’ and caregivers’ characteristics [ 18 , 19 , 20 ]. A systematic review revealed that (i) caregivers’ mental health and (ii) time and effort of caregiving responsibilities were associated with caregivers’ burden [ 4 ].…”
Section: Introductionmentioning
confidence: 99%